Microcrack self-repairing microcapsule as well as preparation method and application thereof

Through the combination of nano-carbon powder modified capsule wall material and capsule core materials such as cycloane oil, microcapsules that can quickly heat up and effectively repair microcracks on asphalt pavement under microwave radiation environment are prepared, solving the self-repair efficiency in the prior art Low problem.

CN119432004APending Publication Date: 2025-02-14CHANGAN UNIV +1
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411578312.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

In the case of low temperature environment or insufficient stress at the crack tip, it is difficult to ensure that the capsule core material quickly fills micro-cracks, resulting in low self-healing efficiency.

Method used

Using nano-carbon powder modified capsule wall material, combined with cycloalkane oil, kerosene and 1000CS dimethyl silicone oil as capsule core material, microcrack self-healing microcapsules are prepared through ultrasonic dispersion and drying processes, and absorbing is used in microwave radiation environment. The heating material accelerates the release of the capsule core material.

Benefits of technology

It significantly improves the wave absorption and heating performance and mechanical properties of microcapsules, enhances the self-repair efficiency in low-temperature environments, and can quickly repair road microcracks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119432004A_ABST
    Figure CN119432004A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of asphalt pavement repairing materials, and particularly relates to a micro-crack self-repairing microcapsule as well as a preparation method and application thereof. The microcapsule comprises a capsule wall and a capsule core, the capsule wall is prepared from methylated melamine-formaldehyde resin and a modifier, and the modifier is selected from nano carbon powder. The microcapsule has excellent wave-absorbing and temperature-rising performance, has relatively good thermal stability and mechanical properties, and can efficiently repair pavement microcracks.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of asphalt pavement repair materials, and in particular relates to a microcrack self-repairing microcapsule and a preparation method and application thereof. Background Art

[0002] Asphalt pavement is prone to tiny cracks under the influence of long-term vehicle loads and external environment. Since they cannot be detected during the service life of the pavement, they are easily ignored. Under the influence of external loads and environment, micro cracks will further crack into macro cracks, which will cause mud pumping, slurry boiling and other pavement diseases, seriously affecting the service performance and service life of the asphalt pavement. Therefore, the treatment of micro cracks in asphalt pavement cannot be ignored.

[0003] At present, the existing technology has proposed a variety of asphalt pavement self-healing technologies, including passive self-healing technologies such as electromagnetic induction heating and microwave induction heating, as well as active self-healing technologies such as polymer fibers and microcapsules. Among them, microcapsule technology is considered to be an effective method to improve self-healing performance due to its simple preparation process and high healing efficiency. The mechanism of action of traditional microcapsules is that when microcracks appear inside the asphalt pavement, the microcapsules will rupture under the action of their tip stress, releasing the capsule core material with a repairing effect. The core material flows to the asphalt around the microcracks through free penetration, diffusion and capillary effects, thereby achieving the purpose of microcrack healing. However, under certain special conditions (such as low temperature environment, or the stress at the crack tip is not enough to rupture the microcapsule, etc.), the single mechanism mode of releasing the capsule core material only through the crack tip stress cannot ensure that the capsule core material quickly fills the microcracks. Therefore, it is very necessary to develop microcapsules that stimulate the release of capsule core materials.

[0004] Studies have shown that temperature is a major factor affecting the diffusion and filling efficiency of the core material in microcracks. Increasing the external temperature of the microcapsule can enhance the self-healing efficiency of the core material to a certain extent. In addition, asphalt is a temperature-sensitive material. Increasing the temperature of the asphalt around the microcracks also helps to enhance the diffusion of asphalt molecules, thereby stimulating the closure of microcracks. Therefore, the use of temperature to stimulate the release of the core material is considered to be an effective mode for achieving timely rupture and healing of microcracks in microcapsules. Introducing microwave-absorbing heating materials into the capsule wall allows the capsule to heat up rapidly under the stimulation of a microwave radiation environment, accelerating the release of the core material and enabling more efficient repair of microcracks. Summary of the invention

[0005] The present invention has developed a microcrack self-repairing microcapsule, which has excellent wave absorption and heating performance, good thermal stability and mechanical properties, and can efficiently repair pavement microcracks.

[0006] In order to achieve the above object, the present invention can adopt the following technical solutions:

[0007] On one hand, the present invention provides a microcrack self-repairing microcapsule, comprising a capsule wall and a capsule core. The raw materials for preparing the capsule wall include methyl etherified melamine-formaldehyde resin and a modifier, and the modifier is selected from nano carbon powder.

[0008] Preferably, the mass of the above-mentioned modifier is 2.5%-10% of the mass of the capsule wall.

[0009] Preferably, the raw materials for preparing the capsule wall further include an emulsion stabilizer.

[0010] Preferably, the raw materials for preparing the capsule core include naphthenic oil, kerosene and 1000CS dimethyl silicone oil.

[0011] Preferably, the mass ratio of naphthenic oil, kerosene and 1000CS dimethyl silicone oil is (4.5-5.5):(2.5-3.5):1.

[0012] Another aspect of the present invention provides a method for preparing the microcrack self-repairing microcapsules of the present invention, comprising: (1) mixing the raw materials for preparing the capsule core with an emulsifier and performing ultrasonic dispersion to obtain an emulsion; mixing the raw materials for preparing the capsule wall to obtain a capsule wall solution; and (2) mixing the emulsion and the capsule wall solution, ultrasonically dispersing, filtering, and drying to obtain the microcrack self-repairing microcapsules.

[0013] Preferably, in the above step (1), one or more combinations of the following conditions are met:

[0014] Condition (a): The method for preparing the capsule wall solution comprises:

[0015] (i) mixing 1000CS dimethyl silicone oil and a surfactant, adjusting the temperature, adding a modifier under ultrasonic dispersion conditions to obtain a modifier suspension, and then adding the modifier suspension to an extruder to extrude to obtain a uniform modifier suspension; mixing a melamine-formaldehyde resin and / or ethanol with water to obtain a prepolymer solution;

[0016] (ii) mixing the uniform modifier suspension and the prepolymer solution to obtain a capsule wall solution;

[0017] Condition (b): the emulsifier is styrene-maleic anhydride copolymer;

[0018] Condition (c): After mixing the raw materials for preparing the capsule core with the emulsifier, adjusting the pH, swelling in a constant temperature water bath at 60° C., then adding the raw materials for preparing the capsule core and performing ultrasonic dispersion to obtain an emulsion; the pH is 10;

[0019] Condition (d): The ultrasonic dispersion time is 15 min.

[0020] Preferably, in the above condition (a), the mass ratio of 1000CS dimethyl silicone oil to surfactant is (99-106):(3-7); and / or the temperature is 45°C; and / or the ultrasonic dispersion time is 15 min.

[0021] Preferably, in the above step (2), one or more combinations of the following conditions are met:

[0022] Condition (a): Add curing agent during mixing;

[0023] Condition (b): a curing agent is added during the mixing process, the curing agent includes ammonium sulfate and sodium acetate, and the mass ratio of ammonium sulfate to sodium acetate is (1-3):(20-30);

[0024] Condition (c): the emulsion and the capsule wall solution are mixed, the pH value is adjusted, the mixture is heated in a water bath and ultrasonically dispersed, filtered, and dried to obtain the microcrack self-repairing microgel; the pH value is 4.2-4.5 and / or the water bath heating temperature is 70° C.-80° C.;

[0025] Condition (d): Ultrasonic dispersion time is 1 h.

[0026] In another aspect, the present invention provides an asphalt material, which includes the microcrack self-repairing microcapsules of the present invention.

[0027] The beneficial effects of the present invention include at least:

[0028] (1) Compared with other asphalt micro-damage self-repairing microcapsules prepared by in-situ polymerization, the micro-crack self-repairing microcapsules provided by the present invention can achieve a heating rate of 5.89°C / min under microwave radiation environment, and have excellent microwave absorption and heating characteristics, further improving the efficiency of microcapsules in repairing asphalt microcracks.

[0029] (2) The addition of modified materials to the microcrack self-repairing microcapsules provided by the present invention significantly improves the thermal stability and mechanical properties of the capsule wall material.

[0030] (3) Compared with other asphalt micro-damage self-repairing microcapsules prepared by in-situ polymerization, the microcrack self-repairing microcapsules provided by the present invention have a simpler preparation process and the time required for preparing the microcapsules is greatly reduced by about 3 hours. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a process flow chart of preparing a nano-carbon powder-modified road microcrack self-repairing microcapsule capable of absorbing waves and raising temperature according to an embodiment of the present invention;

[0032] Figure 2This is a finished product of the nano-carbon powder-modified road microcrack self-repairing microcapsules capable of absorbing waves and raising temperature prepared by the present invention;

[0033] Figure 3 This is a fluorescence microscopic image of the road microcrack self-repairing microcapsules modified with nano-carbon powder and capable of absorbing microwaves and raising temperatures, prepared in Example 3 of the present invention;

[0034] Figure 4 This is a particle size distribution diagram of the road microcrack self-repairing microcapsules modified with nano-carbon powder and capable of absorbing waves and raising temperature, prepared in Example 1 of the present invention;

[0035] Figure 5 Scanning electron microscope images of the road microcrack self-repairing microcapsules modified with nano-carbon powder and capable of absorbing waves and raising temperature prepared in Examples 1-4 of the present invention and Comparative Example 1;

[0036] Figure 6 This is a thermogravimetric curve of the microcrack self-repairing microcapsules for asphalt roads prepared in Example 3;

[0037] Figure 7 This is a self-healing effect diagram of asphalt mixture added with micro-crack self-repairing microcapsules prepared in Example 3;

[0038] Figure 8 This is a self-healing effect diagram of asphalt mixture added with micro-crack self-repairing microcapsules prepared in Comparative Example 1;

[0039] Fig. 9 This is a diagram showing the self-healing effect of asphalt mixture added with micro-crack self-repairing microcapsules prepared in Comparative Example 2. DETAILED DESCRIPTION

[0040] The examples are provided to better illustrate the present invention, but the present invention is not limited to the examples. Therefore, those skilled in the art may make non-essential improvements and adjustments to the implementation scheme according to the above invention content, which still fall within the protection scope of the present invention.

[0041] The terms used herein are only used to describe specific embodiments and are not intended to limit the present disclosure. Unless the context has a significantly different meaning, expressions in the singular include expressions in the plural. As used herein, it should be understood that terms such as "include", "have", "include" are intended to indicate the presence of features, numbers, operations, components, parts, elements, materials or combinations. The terms of the present invention are disclosed in the specification, and are not intended to exclude the possibility that one or more other features, numbers, operations, components, parts, elements, materials or combinations thereof may exist or may be added. As used herein, " / " may be interpreted as "and" or "or", depending on the circumstances.

[0042] The embodiment of the present invention provides a microcrack self-repairing microcapsule, comprising a capsule wall and a capsule core. The raw materials for preparing the capsule wall include methyl etherified melamine-formaldehyde resin and a modifier, and the modifier is selected from nano carbon powder.

[0043] It should be noted that the self-repairing microcapsules in the present invention have excellent wave absorption and heating performance, good thermal stability and mechanical properties, and can efficiently repair microcracks in the road surface.

[0044] In some specific examples, the mass of the above-mentioned modifier is 2.5%-10% of the mass of the capsule wall, such as 3%, 5%, 7% or 9.

[0045] In some specific examples, the raw materials for preparing the capsule wall further include an emulsion stabilizer; the emulsion stabilizer can be ethylene glycol.

[0046] In some specific examples, the raw materials for preparing the capsule core include cyclohexane oil, kerosene and 1000CS dimethyl silicone oil.

[0047] In some specific examples, the mass ratio of cyclohexane oil, kerosene and 1000CS dimethyl silicone oil is (4.5-5.5):(2.5-3.5):1, such as 5:3:1, 4.8:3.6:1 or 5.2:3.3:1, etc.

[0048] It should be noted that the present invention uses cyclohexane oil, kerosene and 1000CS dimethyl silicone oil as raw materials for the capsule core material. Cyclohexane oil is not only inexpensive but also has good compatibility with asphalt and can effectively restore microcracks; kerosene has better fluidity and can supplement the light components in aged asphalt.

[0049] The embodiment of the present invention also provides a method for preparing the microcrack self-repairing microcapsules of the present invention, comprising: (1) mixing the raw materials for preparing the capsule core with an emulsifier and performing ultrasonic dispersion to obtain an emulsion; mixing the raw materials for preparing the capsule wall to obtain a capsule wall solution; and (2) mixing the emulsion and the capsule wall solution, ultrasonically dispersing, filtering, and drying to obtain the microcrack self-repairing microcapsules.

[0050] In some specific examples, in the above step (1), one or more combinations of the following conditions are met:

[0051] Condition (a): The method for preparing the capsule wall solution comprises:

[0052] (i) mixing 1000CS dimethyl silicone oil and a surfactant, adjusting the temperature, adding a modifier under ultrasonic dispersion conditions to obtain a modifier suspension, and then adding the modifier suspension to an extruder to extrude to obtain a uniform modifier suspension; mixing a melamine-formaldehyde resin and / or ethanol with water to obtain a prepolymer solution;

[0053] (ii) mixing the uniform modifier suspension and the prepolymer solution to obtain a capsule wall solution;

[0054] Specifically, 1000CS dimethyl silicone oil can help the modifier to be uniformly dispersed in the reaction system during the in-situ polymerization synthesis process, thereby alleviating the agglomeration of the nano-carbon powder; in addition, the present invention can effectively alleviate the agglomeration of the nano-carbon powder during the in-situ polymerization process after the modifier is dispersed, so that the nano-carbon powder can be more uniformly dispersed in the capsule wall material;

[0055] Condition (b): the emulsifier is styrene-maleic anhydride copolymer;

[0056] Condition (c): After mixing the raw materials for preparing the capsule core with the emulsifier, adjusting the pH, swelling in a constant temperature water bath at 60° C., then adding the raw materials for preparing the capsule core and performing ultrasonic dispersion to obtain an emulsion; the pH is 10;

[0057] Condition (d): The ultrasonic dispersion time is 15 min.

[0058] In some specific examples, in the above condition (a), the mass ratio of 1000CS dimethyl silicone oil and surfactant is (99-106):(3-7), such as 100:4, 102:5 or 103:4, etc.; and / or the temperature is 45°C; and / or the ultrasonic dispersion time is 15 minutes.

[0059] In some specific examples, in the above step (2), one or more combinations of the following conditions are met:

[0060] Condition (a): Add curing agent during mixing;

[0061] Condition (b): a curing agent is added during the mixing process, the curing agent includes ammonium sulfate and sodium acetate, and the mass ratio of ammonium sulfate to sodium acetate is (1-3):(20-30), such as 1.5:25, 1.2:24 or 2:28;

[0062] Condition (c): the emulsion and the capsule wall solution are mixed, the pH value is adjusted, the mixture is heated in a water bath and ultrasonically dispersed, filtered, and dried to obtain the microcrack self-repairing microgel; the pH value is 4.2-4.5; and / or the water bath heating temperature is 70° C.-80° C.;

[0063] Condition (d): Ultrasonic dispersion time is 1 h.

[0064] An embodiment of the present invention further provides an asphalt material, which includes the microcrack self-repairing microcapsules of the present invention.

[0065] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with specific examples, but the content of the present invention is not limited to the following examples.

[0066] 1. Sample preparation

[0067] The synthesis process of the road microcrack self-repairing microcapsules modified by nano-carbon powder and capable of absorbing waves and heating is shown in the figure Figure 1 shown.

[0068] Example 1

[0069] (1) Preparation of emulsion: Deionized water was weighed in a beaker, and 1.80 g of styrene-maleic anhydride copolymer was added to the beaker, and the mixture was stirred until fully dissolved. The pH was adjusted to 10, and the mixture was swollen in a constant temperature water bath at 60° C. Then, 6.53 g of a composite regeneration agent (cyclohexane oil, kerosene and 1000CS dimethyl silicone oil in a mass ratio of 5:3:1) was added and ultrasonic dispersion and emulsification were performed for 15 min to obtain an emulsion;

[0070] (2) Dispersion treatment of nano-carbon powder: 20 g of 1000CS dimethyl silicone oil and 0.6 g of Span 80 surfactant were mixed, the temperature was adjusted to 45°C, 0.64 g of nano-carbon powder was added, and ultrasonic (600W) dispersion was performed for 5 min to obtain a nano-carbon powder suspension. The suspension was further added to a SY-6216-B laboratory single-screw extruder and extruded twice to obtain a uniform nano-carbon powder suspension.

[0071] (3) Preparation of prepolymer solution: 8.07 g of high-methyl etherified melamine-formaldehyde resin and 0.12 g of ethylene glycol were weighed, added to 100 g of deionized water, and stirred thoroughly to obtain a prepolymer solution;

[0072] (4) Preparation of nano-carbon powder modified capsule wall: slowly adding the uniform nano-carbon powder suspension prepared in step (2) to the prepolymer solution of (3) (the volume ratio of the nano-carbon powder suspension to the prepolymer solution is 1:5), and fully stirring to obtain a modified capsule wall solution;

[0073] (5) Synthesis of microcapsules: The modified capsule wall solution in step (4) was transferred to the emulsion prepared in step (1), and a composite curing agent aqueous solution (5.31 g of sodium acetate, 0.19 g of ammonium sulfate and 200 g of deionized water) was added. Then, a 10% acetic acid solution was slowly added at a rate of 3 ml / min to adjust the pH value to 4.3. The water bath temperature was gradually increased from 15°C to 75°C at a rate of 1.5°C / min. Ultrasonic dispersion (300W) was performed for 1 hour to obtain a microcapsule suspension. The suspension was repeatedly washed twice with deionized water and trichloroethylene, then filtered, and dried with a blower for 1 hour to obtain microcrack self-repairing microcapsules.

[0074] Example 2

[0075] The difference between Example 2 and Example 1 is that in Example 2, 0.64 g of nano-carbon powder in Example 1 is replaced by 0.48 g of nano-carbon powder, and the other steps are the same as in Example 1.

[0076] Example 3

[0077] The difference between Example 3 and Example 1 is that in Example 3, 0.64 g of nano carbon powder in Example 1 is replaced by 0.32 g of nano carbon powder, and the other steps are the same as in Example 1.

[0078] Example 4

[0079] The difference between Example 4 and Example 1 is that in Example 4, 0.64 g of nano carbon powder in Example 1 is replaced by 0.16 g of nano carbon powder, and the other steps are the same as in Example 1.

[0080] Comparative Example 1

[0081] The difference between Comparative Example 1 and Example 1 is that in step (2) of Comparative Example 1, no nano-carbon powder is added, and the other steps are the same as Example 1.

[0082] Comparative Example 2

[0083] The difference between Comparative Example 2 and Example 3 is that in Comparative Example 2, 0.32 g of nano-carbon powder in Example 1 is replaced by 0.32 g of graphene, and the other steps are the same as those in Example 3.

[0084] 2. Sample Characterization

[0085] (I) Finished product picture

[0086] The finished product of the microcrack self-repairing microcapsule prepared in Example 3 is shown in FIG. Figure 2 shown.

[0087] (ii) Fluorescence microscopy images

[0088] The fluorescence microscopic image of the microcrack self-repairing microcapsules prepared in Example 3 is as follows: Figure 3 shown.

[0089] (III) Particle size distribution

[0090] The particle sizes of the microcrack self-repairing microcapsules prepared in Example 1 were statistically analyzed. Figure 4 It can be seen that the particle size distribution is between 40μm-60μm, mainly concentrated between 50μm-60μm, and the particle size distribution is relatively uniform.

[0091] (IV) Scanning electron microscope image

[0092] The scanning electron microscope images of the microcrack self-repairing microcapsules prepared in Examples 1 to 4 and Comparative Examples 1 to 2 are as follows: Figure 5As shown, it can be seen that the capsule wall of the microcapsule prepared after adding nano-carbon powder is rougher and denser, and the particle size is uniform; the particle size of the microcapsule without adding nano-carbon powder is too large, and the capsule wall surface is smooth and not dense enough; and the surface of the microcapsule added with graphene is adhered to a large number of resin blocks, and the formed microcapsules are not uniform and dense enough.

[0093] (V) Basic performance of microcrack self-repairing microcapsules

[0094] The physical properties and chemical composition of the self-repairing material (capsule core material) in the microcrack self-repairing microcapsules prepared in the examples of the present invention and the comparative examples were tested, and the results are shown in Table 1 below.

[0095] Table 1 Basic performance indicators of microcrack self-repairing microcapsule core materials

[0096]

[0097] 3. Sample performance test

[0098] (I) Mechanical properties test

[0099] The microcrack self-repairing microcapsules prepared in Examples 1-4 and Comparative Examples 1-2 of the present invention were tested using nanoindentation testing technology, and the specific steps are as follows:

[0100] (1) Use a glass cutter to cut the slide into 1 cm × 1 cm squares;

[0101] (2) Apply the crystal glue evenly on the cut glass slide, and use a glue spreader to make the glue layer thin and smooth;

[0102] (3) Sprinkling a small amount of microcrack self-repairing microcapsule sample on the above glass slide before the binder solidifies;

[0103] (4) Wrap the sample to be tested with plastic wrap and place it in a culture dish at room temperature for 24 hours. After the binder is completely cured, fix the glass slide with the microcapsules on the loading platform of the nanoindentation test for subsequent testing.

[0104] The test results are shown in Table 2 below.

[0105] Table 2 Young's modulus and nanohardness test results

[0106] Mechanical parameters Example 1 Example 2 Example 3 Example 4 Comparative Example 1 Comparative Example 2 Nanohardness(Gpa) 0.54 0.50 0.39 0.31 0.26 0.29 Young's modulus (Gpa) 3.15 3.07 2.91 2.62 2.45 2.68

[0107] From Table 1 above, it can be seen that the average Young's modulus and average hardness of the microcrack self-repairing microcapsules prepared by the present invention are higher than the corresponding mechanical parameters of the unmodified microcapsules, indicating that using nano-carbon powder as a modifier for microcapsules can effectively improve the mechanical properties of microcapsules and make them have better anti-deformation ability. Compared with graphene-modified microcapsules with the same addition amount, the microcapsules modified with nano-carbon powder have better mechanical properties.

[0108] (II) Thermal stability test

[0109] The microcrack self-repairing microcapsules ( Figure 6 Microcapsules in asphalt regeneration agent and melamine formaldehyde resin, the test results are as follows Figure 6 As shown, the results show that when the temperature is lower than 200°C, the microcrack self-repairing microcapsules hardly experience thermal weight loss and only lose 2.37% of their mass; when the temperature is 300°C, the mass retention rate of the microcrack self-repairing microcapsules can still reach 95%; when the temperature exceeds 325°C, significant mass loss occurs; the above shows that the addition of nano-carbon powder for modification significantly improves the thermal stability of the microcapsules and effectively delays the damage and consumption of the core material by the external high temperature environment.

[0110] (III) Thermodynamic performance test

[0111] The temperature rise of the microcrack self-repairing microcapsules prepared in Examples 1-4 and Comparative Examples 1-2 under different microwave times was observed using an infrared thermal imager, and the specific steps were as follows:

[0112] (1) 10 g of microcrack self-repairing microcapsules were repeatedly rinsed with petroleum ether, then dispersed in anhydrous ethanol, and then placed in a 60 °C oven for 2 h to evaporate the remaining water;

[0113] (2) Spread the microcrack self-repairing microcapsules evenly on the glass slide 1 cm 2 within the area and cover with a coverslip;

[0114] (3) placing the glass slide in a microwave heating cabinet for microwave heating;

[0115] (4) After the microwave heating is completed, an infrared thermal image of the microcapsules is obtained by using an infrared thermal imager. The test results are shown in Table 3.

[0116] Table 3 Temperature rise characteristics of microcapsules under different microwave heating times

[0117]

[0118] It can be seen from Table 3 that the microcrack self-repairing microcapsules prepared by the present invention have excellent wave absorption and heating characteristics; the temperature of the microcapsules that have not been modified with nano-carbon powder has almost no change under the microwave radiation environment; under the same modifier addition amount, the heating rate of the self-repairing microcapsules modified with nano-carbon powder is also much greater than the heating rate of the self-repairing microcapsules modified with graphene, indicating that nano-carbon powder can give the microcapsules excellent wave absorption and heating function.

[0119] In summary, the present invention adopts nano-carbon powder as a modifier for road microcapsules through chemical reaction design to prepare road microcapsules with high capsule core content and uniform particle size, which has a significant improvement effect on the road thermal stability, mechanical properties and self-healing properties of asphalt mixture.

[0120] (IV) Semicircular split loading-healing-loading test

[0121] The microcrack self-repairing microcapsules in Example 3 and Comparative Examples 1-2 with the best microcapsule morphology were prepared into microcapsule asphalt mixture specimens according to the relevant provisions of the "Test Procedure for Asphalt and Asphalt Mixture for Highway Engineering" (JTG E20-2011) at different dosages (mass ratio of microcrack self-repairing microcapsules to asphalt) (0, 3%, 6%, 9% and 12%), and the self-healing performance of the microcapsules in AC-16 and SMA-13 ​​asphalt mixtures was tested. The specific steps are as follows:

[0122] (1) Place the prepared semicircular specimen in a low-temperature test chamber at 0°C for 2 hours and perform the first splitting test. The critical load at this time is recorded as P 0 ;

[0123] (2) Wrap and fix the split semicircular specimen with a mold, then place it in a microwave radiation environment for healing, and after the healing is completed, place it in a 0°C environmental box for insulation for 2 hours;

[0124] (3) Remove the fixed mold and repeat step (1) until the specimen is completely broken. The critical load at this time is recorded as P. 1 .

[0125] The healing index is used to quantify the healing effect of microcapsules on asphalt mixtures;

[0126]

[0127] Test results such as Figure 7-9 As shown, the results show that increasing the amount of microcrack self-repairing microcapsules can significantly enhance the self-healing performance of asphalt mixtures; the microcrack self-repairing microcapsules in Example 3 of the present invention can significantly improve the self-healing performance of asphalt mixtures under microwave radiation conditions.

[0128] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution of the present invention, which should be covered by the scope of the claims of the present invention.

Claims

1. A microcrack self-repairing microcapsule, characterized in that: The invention comprises a capsule wall and a capsule core. The raw materials for preparing the capsule wall comprise methyl etherified melamine-formaldehyde resin and a modifier, and the modifier is selected from nano carbon powder.

2. The microcrack self-repairing microcapsule according to claim 1, characterized in that: The mass of the modifier is 2.5%-10% of the mass of the capsule wall.

3. The microcrack self-repairing microcapsule according to claim 1, characterized in that: The raw materials for preparing the capsule wall also include an emulsion stabilizer.

4. The microcrack self-repairing microcapsule according to any one of claims 1 to 3, characterized in that: The raw materials for preparing the capsule core include naphthenic oil, kerosene and 1000CS dimethyl silicone oil.

5. The microcrack self-repairing microcapsule according to claim 4, characterized in that: The mass ratio of cyclohexane oil, kerosene and 1000CS dimethyl silicone oil is (4.5-5.5):(2.5-3.5):

1.

6. The method for preparing microcrack self-repairing microcapsules according to any one of claims 1 to 5, characterized in that: include: (1) mixing the raw materials for preparing the capsule core with an emulsifier and performing ultrasonic dispersion to obtain an emulsion; and mixing the raw materials for preparing the capsule wall to obtain a capsule wall solution; (2) The emulsion and the capsule wall solution are mixed, ultrasonically dispersed, filtered, and dried to obtain microcrack self-repairing microcapsules.

7. The preparation method according to claim 7, characterized in that: In step (1), one or more of the following conditions are met: Condition (a): The method for preparing the capsule wall solution comprises: (i) mixing 1000CS dimethyl silicone oil and a surfactant, adjusting the temperature, adding a modifier under ultrasonic dispersion conditions to obtain a modifier suspension, and then adding the modifier suspension to an extruder to extrude to obtain a uniform modifier suspension; mixing a melamine-formaldehyde resin and / or ethanol with water to obtain a prepolymer solution; (ii) mixing the uniform modifier suspension and the prepolymer solution to obtain a capsule wall solution; Condition (b): the emulsifier is styrene-maleic anhydride copolymer; Condition (c): After mixing the raw materials for preparing the capsule core with the emulsifier, adjusting the pH, swelling in a constant temperature water bath at 60° C., then adding the raw materials for preparing the capsule core and performing ultrasonic dispersion to obtain an emulsion; the pH is 10; Condition (d): The ultrasonic dispersion time is 15 min.

8. The preparation method according to claim 7, characterized in that: In condition (a), the mass ratio of 1000CS dimethyl silicone oil to surfactant is (99-106):(3-7); and / or the temperature is 45°C; and / or the ultrasonic dispersion time is 15 min.

9. The preparation method according to any one of claims 7 to 8, characterized in that: In step (2), one or more of the following conditions are met: Condition (a): curing agent is added during mixing; Condition (b): a curing agent is added during the mixing process, the curing agent includes ammonium sulfate and sodium acetate, and the mass ratio of ammonium sulfate to sodium acetate is (1-3):(20-30); Condition (c): the emulsion and the capsule wall solution are mixed, the pH value is adjusted, the mixture is heated in a water bath and ultrasonically dispersed, filtered, and dried to obtain the microcrack self-repairing microgel; pH is 4.2-4.5 and / or water bath heating temperature is 70℃-80℃; Condition (d): Ultrasonic dispersion time is 1 h.

10. An asphalt material, characterized in that: The invention comprises the microcrack self-repairing microcapsule as described in any one of claims 1 to 5.

Citation Information

Cited By

  • Graphitized carbon layer modification-based high microwave thermal response aggregate as well as preparation method and application thereof

    CN120208570A

  • Composite hose based on micron-sized self-repairing microcapsule and microwave triggering and preparation and repairing method thereof

    CN121105487A